Pengembangan Perangkat Pembelajaran Kesetimbangan Kimia Berbasis Model Differentiated Science Inquiry untuk Meningkatkan Hasil Belajar Peserta Didik - Utami, Sherly Putri; Ramlawati, Ramlawati; Wijaya, mohammad (Chemistry Education Review (CER), 2021)
This study is research and development aimed to develop chemical equilibriums’ learning materials based on differentiated science inquiry which valid, practical, and effective enhancing students’ learning outcomes. The learning materials was developed by 4-D development model belongs to Thiagarajan which consisted of define, design, develop, and dissiminate phases. It has been validated by expert practitioners, tested limited and field, and revised by developer getting valid, practical, and effective product. The  research result showed that (1) validity assesment of lesson plan, students’ book and worksheet, learning media, and learning aoutcomes test are in valid category; (2) It’s also in fully implemented category, teacher and students’ responses are in very practical and practical category; (3) amount 30 students of XI MIPA 1 SMAN 8 Gowa have average achievement based on learning outcomes test as much as 86,27 with good category from 100 as ideal score, (4) It’s in effective category based on learning outcomes test which the complete percentage is about 83,33%, (5) The enhace of learning outcomes is in high category with N-Gain of 0,736 respectively.